The influence of breeder of broiler chicken age on egg parameters - Dias, Isabella de Camargo; Doi, Ana Carolina Britto; Borsoi, Anderlise; Maiorka, Alex (Archives of Veterinary Science, 2025)
The aim of this study was to determine the effects of the breeder age on egg parameters, such as egg weight, weight at transfer, chick weight at hatch, egg weight loss, egg weight/chick weight, and hatch rate. A total of 1440 eggs from Cobb-500® lineage breeders of different weeks of age were used. The eggs underwent the same hatchery practice conditions, including management, disinfection, storage, and incubation. The experimental design was completely randomized with three treatments (30, 40 to 53 weeks of breeder age) and five replicates of 96 eggs each, totaling 1440 incubated eggs. There were three eggs weighing during the experimental period: before incubation, at transfer to the hatcher, and after 21 days (504 experimental hours). The parameters evaluated were egg weight, weight at transfer, broiler chick weight, hatch rate, egg weight loss, and the ratio between egg weight and chick weight. The results were subjected to analysis of variance and, when significant, to Tukey's test (5%). The breeder's age influenced egg weight, transfer weight, and chick weight at hatching, establishing a positive correlation (p<0.01), where older breeders produced heavier eggs and chicks. There was also a correlation between hatch rate and breeder age, with younger birds showing a higher hatchability than older breeders (p=0.035). It was concluded that the breeder's age influences the weight of the egg and the broiler chick and that younger breeders have higher hatchability compared to older breeders.